p-Dodecylbenzene Sulfonic Acid Catalyzed Simple and Efficient Synthesis of 1,8-Dioxo-decahydroacridines in Aqueous Media - Li, Sheng-Hui; Tang, Chan (Asian Journal of Chemistry, 2011)
p-Dodecylbenzene sulfonic acid (DBSA)-catalyzed synthesis of new fluorinated 1,8-dioxodecahydroacridines is achieved via one-pot, three component condensation of aromatic aldehydes (1), 5,5-dimethyl-1,3-cyclohexanedione (2) and 4-fluoroaniline (3) in aqueous media. This method provides several advantages such as neutral and mild condition, high to excellent yield and simple work-up.